PEMELIHARAAN HUBUNGAN PASANGAN YANG MENIKAH MELALUI PROSES TA’ARUF - Sasaningtawang, Bening; Rahardjo, Turnomo (Interaksi Online, 2019)
Families of couples married through the ta'aruf process have more potential for conflict than married couples through other assessment processes. Not getting to know each other's prospective partners with each other and not yet understanding the daily habits of the partner is one of the factors that can cause potential conflict in the family. Each partner plays an important role in maintaining relationship so that the family stays in harmony. Harmonious family is the dream of every couple, including couples who marry through the ta'aruf process. The existence of a conflict that occurs within the family of a couple who marries through the ta'aruf process must be resolved quickly and well so as not to damage the relationship that has been established. This study aims to find out how to maintain the relationship of married couples through the ta'aruf process through a phenomenological approach. This study uses the foundation of the Relationship Maintenance Theory by Stanford and Canary and the Pattern Interaction Theory by Batseon and Waltzlawick. The data collection technique used in this study is in depth interviews with the subjects of five couples married through the ta'aruf process. The results of this study reveal that each family of married couples through the ta'aruf process has its own way of maintaining relationships, namely in creating positive, optimistic, and open relationships and having guarantees and division of tasks, almost entirely believed by adhering to religious and entrusting what happened to Allah. Conflicts that often occur are unknown habits of each partner and misunderstandings that occur because of suspicion of dealing with others on concerns also about polygamy. The pattern of interactions that occur in each pair tends to be the same, where relationship control is complementary.